Pengaruh Literasi Keuangan Dan Inklusi Keuangan Terhadap Kinerja UMKM Di Kecamatan Moyo Hulu - Arnas Sandani Ghutama; Fahlia Fahlia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the influence of financial literacy and financial inclusion on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Moyo Hulu District. This research employed a quantitative approach using a survey method. The population consisted of MSME owners in Moyo Hulu District, with a sample of 70 respondents determined using the Slovin formula. Data were collected through questionnaires based on a Likert scale. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results of the study indicate that financial literacy and financial inclusion simultaneously have a significant effect on MSME performance. Partially, financial literacy has a positive and significant effect on MSME performance, while financial inclusion does not have a significant effect on MSME performance. These findings suggest that financial literacy plays an important role in improving MSME performance through better financial knowledge, skills, and decision-making abilities. On the other hand, access to financial services alone is not sufficient to improve business performance without the ability to utilize such services effectively. Nevertheless, the combination of financial literacy and financial inclusion still contributes significantly to the improvement of MSME performance in Moyo Hulu District.